Effects of artificial tears on rabbit ocular surface healing after exposure to benzalkonium chloride. (1st October 2016) - Zhang, Yuqiu; Cao, Hong; Lin, Tong; Gong, Lan
Abstract: The aim of the study was to observe the effect of different artificial tears on healing the drug-induced keratopathy. To this aim, 64 rabbits received topical administration of 0.01% benzalkonium chloride to establish models and were divided into four groups. The control group received ocular saline solution (Saline), while the others were treated with Refresh Plus® (RF), Hycosan® (H) and Systane® Ultra (SU). Surface abnormalities were examined daily using slit-lamp. Fluorescein staining, histopathological and transmission electron microscopic (TEM) examination were performed at day 0, 2 weeks, and 1 and 2 months. A significant difference was observed between RF and SU, but not between H and SU at 2 weeks. TEM examination revealed new microvilli close to the cavity surface, and the number of microvilli in SU was greater than in H at 2 weeks and 1 month. Based on the results, the effect in the SU group was the most significant. Eye drops with nontoxic preservative such as SU are an alternative to treat drug-induced keratopathy.